Impact of perioperative anticoagulation on artificial urinary sphincter device survival. (4th July 2017) - Blackburne, Andrew T.; Linder, Brian J.; Elliott, Daniel S.
Abstract: Objective: The aim of this study was to evaluate the impact of perioperative anticoagulation on artificial urinary sphincter (AUS) device outcomes. Methods: Following institutional review board approval, patients undergoing AUS surgery from 1983 to 2014 were evaluated to assess device survival in patients with warfarin use compared to individuals without warfarin use. Hazard regression analysis was used to determine the association between warfarin use and device outcomes. Results: From 1983 to 2014, there were 2125 AUS procedures at Mayo Clinic. Of these, information regarding anticoagulation use was available in 651, including 43 patients who were on warfarin and 608 who were not. On univariate analysis, the use of warfarin was associated with an increased rate of infection/erosion [hazard ratio (HR) 2.58, p = 0.02]. However, there was no increased risk of overall AUS failure (HR 1.66, p = 0.06), malfunction of AUS (HR 1.19, p = 0.74) or urethral atrophy (HR 1.09, p = 0.88). Kaplan–Meier assessment of device survival for individuals not on warfarin versus individuals on warfarin at 1 and 5 years was 91% versus 83% and 72% versus 57%, respectively ( p = 0.058). On multivariate analysis, warfarin was not associated with an increased risk of infection/erosion (HR 1.37, p = 0.51). Conclusion: Perioperative management of AUS patients on warfarin requires expert care; however, long-term AUS device survival is not significantly affected by warfarin use. Recognition of these outcomes is important for improving preoperative patient counseling and surgical patient selection.